2007
DOI: 10.1590/s0103-21002007000300015
|View full text |Cite
|
Sign up to set email alerts
|

Feelings and expectations of mothers of preterm babies at discharge

Abstract: OBJECTIVE: To investigate the feelings and expectations of mothers of preterm babies at discharge. METHODS: This descriptive study used Bardin's framework to collect data among 11 mothers of preterm babies from a Neonatal Intensive Care Unit. Data were collected through interviews from December 2004 to January 2005. RESULTS: Four categories emerged: the moment of the discharge; mothers' knowledge and questions; mothers' preparation and orientation for discharge; and, mothers' desired orientation. CONCLUSION: A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0
4

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(40 citation statements)
references
References 4 publications
2
33
0
4
Order By: Relevance
“…Estudos corroboram esta estratégia ao revelarem que as mães se sentem satisfeitas e confiantes estando presentes na unidade e podendo observar os cuidados prestados ao filho pelos profissionais de saúde. 11 Assim, ressalta-se que a comunicação entre a equipe de saúde e a família é um recurso essencial no processo de adaptação à hospitalização do RN. Fortalecer e estimular o vínculo afetivo são estratégias favorecidas pela comunicação horizontal entre os segmentos mencionados, através da qual se estabelece uma interação efetiva com a família.…”
Section: Cuidar Do Filho: Permanecendo Na Companhia Da Mãeunclassified
“…Estudos corroboram esta estratégia ao revelarem que as mães se sentem satisfeitas e confiantes estando presentes na unidade e podendo observar os cuidados prestados ao filho pelos profissionais de saúde. 11 Assim, ressalta-se que a comunicação entre a equipe de saúde e a família é um recurso essencial no processo de adaptação à hospitalização do RN. Fortalecer e estimular o vínculo afetivo são estratégias favorecidas pela comunicação horizontal entre os segmentos mencionados, através da qual se estabelece uma interação efetiva com a família.…”
Section: Cuidar Do Filho: Permanecendo Na Companhia Da Mãeunclassified
“…At the same time as the parents feel happy and relieved after the infant's discharge, they also feel anxious and insecure 12 about the new care phase that is starting, distant from the hospital team. In the phase they are entering, adaptations and readjustments of the existing family bonds and subsystems are needed, as well as of the roles each family member assumed, with a view to furthering attendance to the infant's needs and his/ her inclusion in the family context.…”
Section: Reflecting On Family Interac-tions and Home Care For The In-mentioning
confidence: 99%
“…The results indicated that mothers reported less stress, depression and anxiety and more positive interactions occurred in the neonatal unit, in addition to the reduction in length of hospital stay of the newborn by almost four days (11) . A study that interviewed mothers of premature infants in a neonatal intensive care unit showed that mothers felt satisfied to be present in the unit, even when just observing the execution of the procedures, because such experience gave them new notions of the care strategy (13) . With the inclusion of mothers in care, it appeared that some nursing professionals perceived such participation as an aid in the reduction of work overload (10) .…”
Section: Participation In Care Of the Preterm Childmentioning
confidence: 99%
“…Moreover, the parents wanted to receive useful information about their child and data reporting on the condition of his health at this time (13) . However, one study stressed, by talking to the professionals interviewed, that during hospital discharge, mothers expressed many emotions and that such emotional burden hindered concentration for learning at that moment (14,16) .…”
Section: Preparation For Hospital Dischargementioning
confidence: 99%
See 1 more Smart Citation